The importance of spider diversity in agroecosystems and the effect of pesticides - Marco Antonio Benamú P (Global Journal of Ecology - Peertechz Publications, 2020)
Several studies show that spiders represent the largest biomass of predatory arthropods in different agroecosystems, which added to their habits increase their potential as the main consumer of certain pest species [1-4]. Their constant and abundant presence during all phases of the development of a crop allows them to act as effective natural enemies of phytophagous insects [3-9], due to the ability to colonize different agroecosystems [8,10,11].